Study on scour simulation and boundary condition conversion technology for a shallow foundation bridge - Gangping Fan; Huanzhe Li; Tianzhuo Wang; Jian Che; Xing Li; Chunyang Dou; Tong Wu (Scientific Reports)
Abstract Bridges with shallow foundations are highly susceptible to flood scouring due to their limited embedment depth and small contact area between the soil and foundation. This can lead to foundation voids, posing a serious threat to bridge safety. To prevent and mitigate scouring risks, this paper investigates the riverbed scouring characteristics of shallow foundation bridges under different hydrological conditions.The study found that under high water levels and flow velocities, scour depth significantly increased.Under extreme hydrological conditions, a horseshoe vortex forms at the base of the front end of the bridge pier, causing scour pits on both sides of the upstream face of the foundation, which is the main cause of foundation voids that first appear at 2580 s with a maximum scour depth of -2.51 m and a void area of 0.5%, continuing to increase over time.Based on simulated scouring data, this study proposes a method for converting boundary conditions from a scouring model to a mechanical model. This method utilizes point cloud reverse engineering technology to generate a riverbed surface from the three-dimensional coordinate matrix of the boundary and import it into the structural analysis field. Hydraulic effects are calculated using a CFD model and transferred to the structural domain through fluid-structure interaction technology, achieving multi-physical field coupling among water flow, soil, and structure. This method addresses the current limitations in simulating complex scouring forms in bridge flood damage research, providing reliable technical support for subsequent studies on the damage behavior of shallow foundation bridges under flood scouring conditions.